Impact of Brand Equity on Patronage and Repurchase Intention of Branded Apparels in Chennai City - V. , Devendranath Reddy; S. , Fabiyola Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
Branding is defined as, establishing an image or reputation in the eyes of customers. The prime purpose of branding is to make your brand exceptional and stands separate among the available brands. Branding may be communicated through corporate color palettes, logo but it is not limited to. Branding also represents store environment, employees, quality, price of the product, advertising and so on. In this paper, the researcher aimed to find out the brand equity and its impact of Repurchase intention of apparel customers of Chennai city. Young customers who age group falls between 18-30 were selected for the study about their preferred brands of apparel for their regular and casual apparel needs.135 samples were collected and data analysis was carried out using IBM SPSS and AMOS 0.0 packages. The results of the study represents that all the five constructs used in the study namely Brand familiarity, Brand Relevance, Brand Exclusivity, Brand performance, Brand Legacy is having an impact and found to be the drivers of repurchase intention.